Influence of different fertilizer application rates on growth and yield components of two maize varieties in a forest-savannah-transition agro - ecology zone (2018)
Field study on the influence of fertilizer application on growth and yield components of maize was carried out in 2015 and 2016 at the Institute of Agricultural Research and Training (I.A.R&T), Ibadan Station. Two maize varieties (ILE-1-OB and TZPBSR-W) were evaluated under three rates of NPK 20-10-10: 0, 50 and 100 kg N ha-1, one rate of Tithonia compost; 10 t ha-1 (representing 10.7 kg N ha-1) and two rates of NPK and Tithonia compost combinations (50 kg N ha-1+10 t ha-1 and 100 kg N ha-1+10 t ha-1) using randomized complete block design (r=3) arrangement. Selected maize plants were assessed for plant height (cm), leaf area (cm2), stem diameter (cm), number of ears per plant, number of rows per cob, number of kernels per row, number of kernels per cob, 1000-kernel weights and grain yield. Various growth and yield components evaluated increased significantly with increased fertilizer application. Combinations of 50 kg N ha-1+ 10 t ha-1 and 100 kg N ha-1+10 t ha-1 enhanced growth and yield performances of maize better than sole applications of 50 or 100 kg N ha-1. Highest grain yield was obtained under 50 kg N ha-1 +10 t ha-1 (5.26, 5.82 t ha-1) and 100 kg N ha-1 + 10 t ha-1 (5.78, 5.91 t ha-1) in 2015 and 2016 respectively. The use of 50 kg N ha-1 inorganic fertilizer in combination with 10 t ha-1 (10.7 kg N ha-1) Tithonia compost adequately enhanced growth and yield performance of maize in the Forest-Savannah-Transition agro - ecology zone of Nigeria.